2016
DOI: 10.3748/wjg.v22.i35.8050
|View full text |Cite
|
Sign up to set email alerts
|

Second-generation direct-acting-antiviral hepatitis C virus treatment: Efficacy, safety, and predictors of SVR12

Abstract: AIMTo gather data on the antiviral efficacy and safety of second generation direct acting antiviral (DAA) treatment with respect to sustained virological response (SVR) 12 wk after conclusion of treatment, and to determine predictors of SVR12 in this setting.METHODSTwo hundred and sixty patients treated with SOF combination partners PR (n = 51), R (n = 10), SMV (n = 30), DCV (n = 81), LDV (n = 73), or 3D (n = 15). 144/260 were pre-treated, 89/260 had liver cirrhosis, 56/260 had portal hypertension with platele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
31
2
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 34 publications
10
31
2
4
Order By: Relevance
“…The median pre-therapeutic viral load was 1,183,000 IU/ mL and 58.2% of patients had a high viral load (≥ 800,000). This result was similar to that found by Werner et al which found an initial high viral load at 65% of cases [23]. This high mean viremia in this study population could be explained by the selection of severe patients in the indexed study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The median pre-therapeutic viral load was 1,183,000 IU/ mL and 58.2% of patients had a high viral load (≥ 800,000). This result was similar to that found by Werner et al which found an initial high viral load at 65% of cases [23]. This high mean viremia in this study population could be explained by the selection of severe patients in the indexed study.…”
Section: Discussionsupporting
confidence: 92%
“…However, the difference in SVR12 was not significant between genotypes. These results were close to those found by Werner et al in 2016 in Germany, which found a 98% SVR12 for genotype 4 [23]. Cirrhotic patients responded significantly less well with 71% SVR12.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Utilizou-se a média da taxa de RVS 12 semanas após o fim do tratamento, considerando seis artigos publicados previamente ao início deste trabalho (POL et al, 2017;SULKOWSKI et al, 2014;JI et al, 2016;WERNER et al, 2016;BECK;KIM;KHALILI, 2016;DAHARI et al, 2016). Estes artigos referem-se a estudos realizados com objetivos similares e em um contexto semelhante ao proposto por esta pesquisa.…”
Section: Cálculo Amostralunclassified
“…). Um estudo de coorte alemão demonstrou que 92% dos pacientes que utilizaram SOF e DCV alcançaram RVS, enquanto 93% dos pacientes que utilizaram SOF e SMV alcançaram RVS(WERNER et al, 2016). Em estudo de vida real brasileiro realizado por Ferreira e colaboradores, o uso de tratamentos compostos por SOF e DCV proporcionou taxas de RVS de aproximadamente 95%, enquanto as taxas de RVS com o uso de SOF e SMV foram de aproximadamente 92%(FERREIRA et al, 2018).A tabela 6 descreve as taxas de RVS dentro de cada variável analisada, separadas por esquema de tratamento utilizado.…”
unclassified